Collective effect of ternary nano fuel blends on the diesel engine performance and emissions characteristics. (1st June 2021) - Fayaz, H.; Mujtaba, M.A.; Soudagar, Manzoore Elahi M.; Razzaq, L.; Nawaz, Saad; Nawaz, Muhammad Ahsan; Farooq, M.; Afzal, Asif; Ahmed, Waqar; Khan, T.M. Yunus; Bashir, Shahid; Yaqoob, Haseeb; et al.
Graphical abstract: Highlights: Palm biodiesel production parameters optimized utilizing the Response Surface Methodology. The maximum BTE recorded for B30 + Al2 O3 compared to other tested blends at all the test conditions. The minimum CO level observed for B30 + TiO2 as compared to other biodiesel blends at 2300 rpm. B30 + CNT indicated a significant reduction in NOx intensity as compared to other blends. Palm biodiesel blended with nanoparticle additives improved engine performance. Abstract: The present study aims to evaluate the emission and performance characteristics of a CI engine using biodiesel blends with three different nanoparticles. Biodiesel was prepared from palm oil using transesterification process. Biodiesel yield has been optimized using response surface methodology, which develops an interaction among the independent operating parameters reaction temperature methanol to oil ratio, and catalyst concentration, where they are changed as follows: 50–65 °C, 5:1–12:1, and 0.25–1.75, respectively. Nano fuel blends were prepared by dispersing CNT, TiO2 and Al2 O3 nanoparticles into the B30 blend. The stability of these nanoparticles was improved by adding sodium dodecyl sulfate (SDS) as a surfactant, and the stability was characterized by ultraviolet–visible spectrometry. These nanoparticles were mingled with palm methyl ester at a proportion of 100 ppm using an ultrasonication water bath. The engine performance and emission characteristics were determined at varying engine speed and a full load condition. At all engine speeds, B30 with Al2 O3 ternary fuel blend exhibits a promising reduction in brake specific fuel consumption (BSFC) of 5.98%. A significant improvement of 9.83%, 3.91% and 1.37% in brake thermal efficiency (BTE) has been observed for Al2 O3, CNT, and TiO2 additives as compared to B10 blend, respectively. B30 with TiO2 ternary blend shows a sharp reduction of 27.89% and 30.68% in the CO and HC emissions respectively, and 10.37% decrease in NOx level with the addition of CNT as a fuel additive in the ternary fuel blend. Palm biodiesel blended with nanoparticle additives enhanced both engine performance and emission characteristics.